“Will AI steal my glory?”: Power relations perceived by college instructors when grappling with Generative AI (Journal of Applied Learning and Teaching, 2026)
This instrumental case study explores college instructors’ perceptions of Generative AI as a potential tool for students to learn writing and their teaching practices under the influence of different power centers. Through inductive analysis, this study identifies four centers that have shaped the college instructors’ perceptions of Generative AI, including the global impact of AI, the university and department, colleagues, and students. In response to these power dynamics, many instructors have updated their teaching practices to make sure that they still retain their authority in class and promote student accountability for their own learning. These changing practices may range from limiting the possibilities of using Generative AI in assignments to actively integrating it into their lesson planning. Findings of this study can inform instructors’ professional development and strategies for responding to the trend of Generative AI in teaching practices.